Linking genetic merit to sparse behavioral data: behavior and genetic effects on lamb growth in Soay sheep. (20th October 2019) - Regan, Charlotte E; Pemberton, Josephine M; Pilkington, Jill G; Smiseth, Per T; Wilson, Alastair J
Abstract: Wild quantitative genetic studies have focused on a subset of traits (largely morphological and life history), with others, such as behaviors, receiving much less attention. This is because it is challenging to obtain sufficient data, particularly for behaviors involving interactions between individuals. Here, we explore an indirect approach for pilot investigations of the role of genetic differences in generating variation in parental care. Variation in parental genetic effects for offspring performance is expected to arise from among-parent genetic variation in parental care. Therefore, we used the animal model to predict maternal breeding values for lamb growth and used these predictions to select females for field observation, where maternal and lamb behaviors were recorded. Higher predicted maternal breeding value for lamb growth was associated with greater suckling success, but not with any other measures of suckling behavior. Though our work cannot explicitly estimate the genetic basis of the specific traits involved, it does provide a strategy for hypothesis generation and refinement that we hope could be used to justify data collection costs needed for confirmatory studies. Here, results suggest that behavioral genetic variation is involved in generating maternal genetic effects on lamb growth in Soay sheep. Though important caveats and cautions apply, our approach may extend the ability to initiate more genetic investigations of difficult-to-study behaviors and social interactions in natural populations. Lay Summary: We followed the behavior of mothers whose genetics were associated with faster/slower lamb growth, finding that lambs from the former had higher suckling success but did not vary in other suckling measures. This suggests that variation in maternal behavior contributes to the maternal genetic effect on lamb growth. Although our approach is reliant on some important assumptions, we hope it will provide a tool to further study genetic variation in difficult-to-study traits in wild populations.